Bkaʼ brgyud Yid bźin nor bu yi ʼphreṅ ba : a precious rosary of lives of eminent masters of the ʼBri-guṅ-pa Dkar-brgyud-pa tradition - O-rgyan-pa Seṅ-ge-dpal, 1229 or 30-1309 (Smanrtsis shesrig spendzod, 1972)
Hagiographies of successive teachings of the Drigungpa sect of Tibetan Lamaism; includes biographical material for lamas of the monastery of Śo-dgon in Khams.